2020
DOI: 10.1098/rspb.2020.1410
|View full text |Cite
|
Sign up to set email alerts
|

Frictional internal work of damped limbs oscillation in human locomotion

Abstract: Joint friction has never previously been considered in the computation of mechanical and metabolic energy balance of human and animal (loco)motion, which heretofore included just muscle work to move the body centre of mass (external work) and body segments with respect to it. This happened mainly because, having been previously measured ex vivo , friction was considered to be almost negligible. Present evidences of in vivo damping of limb oscillations, motion cap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…Interestingly, similar modifications of the control of locomotion were observed when the imbalance between positive and negative work was generated by a horizontal traction force (Dewolf et al, 2020). These results suggest that, though factors other than work also clearly influence the preferred movement strategy, the choice of gait pattern largely depends on the mechanical work that must be Minetti et al, 2020). Finally, CoT is calculated from the ratio of net oxygen consumption (above resting values) and horizontal velocity (red box).…”
Section: New Findingsmentioning
confidence: 72%
See 1 more Smart Citation
“…Interestingly, similar modifications of the control of locomotion were observed when the imbalance between positive and negative work was generated by a horizontal traction force (Dewolf et al, 2020). These results suggest that, though factors other than work also clearly influence the preferred movement strategy, the choice of gait pattern largely depends on the mechanical work that must be Minetti et al, 2020). Finally, CoT is calculated from the ratio of net oxygen consumption (above resting values) and horizontal velocity (red box).…”
Section: New Findingsmentioning
confidence: 72%
“…The effects of such a bias, in real locomotion, will depend on gait type and on the fractional mass of limbs with respect to the whole body, but the exact amount still needs to be substantiated. The new measurements of frictional W INT (Minetti et al, 2020), by completing the work balance of locomotion, should help shed light on the interplay between W INT and W EXT in different gait paradigms (Figure 1). Finally, there is still no gold standard in the literature that deterministically considers all parts of mechanical work (and their 'interdependence').…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…This is not the case in the present study, as we define the optimal speed as that of the minimum mechanical energy expenditure, W ext . Several studies showed that other mechanical work must contribute to the metabolic energy output: (1) the internal work as a result of the kinetic energy changes of the limbs relative to the center of mass (Cavagna and Kaneko, 1977), (2) the work to redirect the center of mass velocity from one inverted pendulum to the other (Donelan et al, 2001(Donelan et al, , 2002a, (3) the internal work done by one leg against the other during double contact (Bastien et al, 2003) and (4) the internal work done against frictional losses (Minetti et al, 2020). Furthermore, the optimal speed determined by the minimum W ext differs between subjects (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This is because walking with shortened steps causes an elevated cost of swinging the legs due to the increased cadence (Doke et al ., 2005; Minetti et al ., 1995). Leg swing at a high cadence is particularly costly as it requires a large amount of internal work performed by muscles to rapidly accelerate the limbs with respect to the COM while overcoming limb friction (Cavagna and Kaneko, 1977; Minetti et al ., 2020). Walking with lengthened steps causes an elevated cost associated with redirecting the body's COM (Adamczyk and Kuo, 2009; Cavagna and Franzetti, 1986; Donelan et al ., 2002; Kuo et al ., 2005).…”
Section: Discussionmentioning
confidence: 99%